Perbedaan Jumlah Trombosit Pada Sampel Darah Yang Dihomogenisasi Sekunder Secara Inversi 2 Kali Dan 8 Kali Setelah Didiamkan Selama 30 Menit Dengan Hematology Analyzer - Elza Angraini; Rosnita Sebayang; Mustika Sari Hutabarat (Fakultas ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
Examination of platelets is an examination that is often asked to be examined by doctors. Homogenization enters into the pre-analytical stage. Homogenization is the mixing evenly between blood and anticoagulants. Homogenization in the laboratory must be carried out properly according to existing procedures so as not to affect the examination results. After the blood is homogenized initially or primary homogenized after blood sampling, a delay in examination is carried out which causes the blood to precipitate, so it is necessary to homogenize after the blood has settled or secondary homogenization so that the blood is homogeneous when it is examined. Secondary homogenization does not yet have standard provisions. To find out the difference in the results of the platelet count examination in the secondary homogenization technique 2 and 8 times. This research is a quantitative observational study with cross sectional and total sampling technique. Samples were homogenized primary 10 times and left for 30 minutes, then samples were homogenized secondary 2 times and 8 times. Platelet counts were checked using the Sysmex XP-100. Data were analyzed using the Paired Sample T-Test with a 95% confidence level. 2 times secondary homogenization has a mean value of 297.06 x 103 / µL and 8 times secondary homogenization has a mean value of 296 x 103 / µL. The data is normally distributed and the hypothesis test is continued, namely the Paired Sample T- Test and the probability results are 0.655 > 0.05, which means there is no difference. Based on the results of the study it can be concluded that there is no difference in the number of platelets in the secondary homogenization of the inversion technique 2 times and 8 times. Further research is recommended to increase the number of research samples with methods and principles, volume variations and variations in sample treatment so that broader and varied research can be useful as a consideration for use in the laboratory